Printed semi-transparent large area organic photovoltaic modules with power conversion efficiencies of close to 5 % - Lucera, L.; Machui, F.; Schmidt, H. D.; Ahmad, T.; Kubis, P.; Strohm, S.; Hepp, J.; Vetter, Andreas; Egelhaaf, H. -J.; Brabec, Christoph (Organic Electronics, 2017)
Currently, certified lab scale organic photovoltaic (OPV) cells reach efficiencies of more than 12% and life times of 10 years. For commercialization, it is necessary to understand which performance can be reached in fully printed large scale products. Our investigations show that large area, semi-transparent organic photovoltaic modules based on industrially available materials can achieve power conversion efficiencies of more than 4.8% on rigid substrates and 4.3% on flexible ones. The modules processed with a combination of large area coating and laser patterning with an active area of 68.76 cmfor flexible modules and a total area of 197.4 cmfor glass modules offer exceptionally high geometric fill factors of more than 94% and a transparency of more than 10%. The processing recipe and the layout of the modules are based on indications of optical and electrical simulations which allow to produce devices with only negligible losses in comparison to small single cell devices. Losses due to imperfect coating or patterning are identified by thermal imaging.
Keywords: Large area processing; Module; Organic photovoltaics; Renewable energy; Semi-transparent; Slot-die coating